Do private signals of a bank s creditworthiness predict the bank s CDS price? Evidence from the Eurosystem's overnight loan rates - Eero Tölö; Esa Jokivuolle; Matti Virén (Bank of Finland, 2014)
We investigate the relationship between the daily average interbank overnight borrowing rate (AOR) and the credit default swap price (CDS) of 60 banks using the Eurosystem's proprietary data from mid-2008 to mid-2013. We find that the AOR which is observable only by the competent Eurosystem authorities leads the CDS at least by one day. The lead was concentrated on days of market stress for banks which mainly borrow from "relationship" lender banks. Such borrower banks are typically smaller, have weak ratings, and likely reside in crisis countries.
URN:NBN:fi:bof-20140807231
Keywords: 330